Salting-out assisted liquid-liquid extraction method coupled to gas chromatography for the simultaneous determination of thujones and pulegone in beverages - Alshishani, A.A. (Taylor and Francis Inc., 2018)
A fast, simple and sensitive salting-out assisted liquid-liquid extraction method for the simultaneous determination of thujones and pulegone in beverage samples was developed. The extraction was achieved by adding ammonium sulphate to a miscible mixture of sample (10Â mL) and acetonitrile (1.5Â mL). The upper layer was directly injected into a capillary gas chromatography unit and detected using flame ionisation detector. The method was validated and calibration curve was linear with r2Â >Â 0.99 over the range of 0.1â15Â mg.kgâ1 and 1â300Â mg.kgâ1 for thujone and pulegone, respectively. The limits of detection were 4.3 and 5.1Â Âµg.kgâ1 and the limit of quantification were 12.9 and 15.3Â Âµg.kgâ1 for thujone and pulegone, respectively. The relative standard deviation for inter- and intra -day precision was less than 10.1. The proposed method was conveniently applied for the determination of these compounds in various herbal and fruit drinks, alcoholic beer and soft drinks. The average recoveries of the analyzed compounds ranged from 97 to 110 for thujone and from 87 to 119 for pulegone in three types of beverages. Thujones were not detected in all the 43 samples analysed while pulegone was detected in two samples (< quantitation limit and 1.78Â mg.kgâ1). Positive identification of the thujone and pulegone peaks were provided by GC-MS. Â© Anas Adib Alshishani, Bahruddin Saad, Nadhiratul Farhin Semail, Salizawati Mohamad Salhimi, and Mohd Khairuddin Mohd Talib.